Introduction to the Special Issue: Theory and Practice of Connectivity in the Indo-Pacific—Spheres, Logics, and Regional Dynamics - Gaens Bart; Sinkkonen Ville; Ruokamo Anu (Springer Nature, 2025)
This short introduction to the Special Issue entitled “Theory and Practice of Connectivity in the Indo-Pacific – Spheres, Logics, and Regional Dynamics” serves four objectives. It first briefly outlines the rationale for theoretical and empirical engagement with the concept of connectivity, which has become a ubiquitous term in the policy parlance of key global actors in recent years. The introduction then provides a short leader on the connectivity initiatives of key players, specifically China, the USA, Japan, the European Union, and Russia, with a particular focus on the Indo-Pacific space. Third, the seven articles that comprise the Special Issue are summarised. The contributions include a theoretically and conceptually oriented lead article, which introduces an analytical framework for the study of connectivity, and six more empirically motivated contributions that draw upon the said framework. Finally, key takeaways arising from the articles with respect to a broader research agenda on connectivity are discussed.